Graduates' Experiences of Transition and Transformation Following Completion of a Nursing Bridging Education Program - Sue Coffey; Gail Lindsay; Katherine Cummings; Shelley Bouchard; Marianne Cochrane; Karen Macdonald; Sandra Mairs; Susan Sproul (Archives of Nursing Practice and Care - Peertechz Publications, 2017)
Background: Nursing bridging education (NBE) refers to educational programs that support learners to move from one level of educational preparation or practice to another. In the context of this study, NBE refers specifi cally to an educational focus that creates the opportunity for learners to move from practice as a college diploma prepared RPN to an RN through earning a Bachelor of Science in Nursing (BScN) degree. Purpose: All participants were asked to respond to four questions that focussed on the impact and outcomes of the NBE program and their experiences transitioning into RN practice. Results: Participants provided insight into their experiences as they were asked to refl ect on the NBE program and their subsequent practice. NBE program graduates describe undertaking an external  process of role transition as they become employed as RNs, while undergoing an internal process of personal and professional transformation through the experience of RN role enactment. Conclusions: Understanding the transformational nature of an educational program is important in harnessing the potential for education to impact not only the learner, but potentially the profession into which students enter upon graduation.